Myers-Briggs Type Indicator (MBTI) - Nosheen Zehra; Sana Jafrani (ziauddin University, 2024)
The Myers-Briggs Type Indicator (MBTI) is a personality assessment test that measures the psychological preferences of different people and helps them identify their strengths and limitations, interests and satisfaction to make right choices. The history of MBTI is unique and interesting, it was inspired by the work of Carl Gastav Jung, a Swiss psychiatrist who proposed psychological types theories which described how people are innately different both in terms of how they perceive and take in information and how they make decisions. The MBTI instrument was initially designed by Katharine Cook Briggs and her daughter Isabel Briggs Mayers after their research on their work on different personality types theories...